2023
DOI: 10.3390/ijerph20054188
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phytochemicals and Plant-Based Diets in Gestational Diabetes: Evidence from Clinical Trials

Abstract: Gestational diabetes mellitus (GDM) is defined as glucose intolerance identified during pregnancy. The increased risk of pregnancy complications and the adverse health effects for the mother and baby associated with GDM require urgent and effective ways to control the condition. The primary goal of this semi-quantitative review was to examine the effects of phytochemicals and plant-based diets on GDM in clinical studies involving women undergoing pregnancy and to summarize the findings for application in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…109,160,161 It is necessary to formulate reasonable clinical intervention measures, including clinical trials of polyphenol-based diets or food groups, dietary polyphenol-based supplements, and pure polyphenolic compounds. 162…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…109,160,161 It is necessary to formulate reasonable clinical intervention measures, including clinical trials of polyphenol-based diets or food groups, dietary polyphenol-based supplements, and pure polyphenolic compounds. 162…”
Section: Discussionmentioning
confidence: 99%
“…109,160,161 It is necessary to formulate reasonable clinical intervention measures, including clinical trials of polyphenol-based diets or food groups, dietary polyphenol-based supplements, and pure polyphenolic compounds. 162 Polyphenols are generally considered safe for use in adults. However, little data have been generated in human clinical studies to demonstrate the safety of polyphenols in pregnant or lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials revealed that phytochemicals and plant-based diets can reduce hyperglycemia in patients with GDM as well as those at high risk of developing GDM. 40 Zhang et al 11 report that oleuropein, a major phenolic component of Olea europaea L., improves GDM via activating AMPK signaling. Astragaloside IV, the main active component of Astragalus membranaceus , alleviates GDM by targeting NLRP3 inflammasome in db/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that vegetarianism can increase nitric oxide bioavailability and decrease reactive oxygen species [6]. The semiquantitative review conducted by Jaworsky et al of women with high risk for GDM pointed out that a plant-based diet and phytochemicals may reduce blood glucose and improve antioxidant activity to reduce the oxidative stress that is often associated with GDM [21]. Also, plant-rich meals significantly increase the serum levels of glucagon-like peptide-1 (GLP-1), a hormone that augments the secretion of insulin [6].…”
Section: Discussionmentioning
confidence: 99%